Synthesis of Functional Tripodal Thioacetates - Kretschmer, Florian; Hager, Martin D.; Schubert, Ulrich S. (Synthesis, 2014)
A versatile route for the synthesis of tripodal thioacetates is reported. Based on the esterification of commercial pentaerythritol tribromide, the method enables the easy introduction of different functional moieties, e.g., into self-assembled monolayers.
Keywords: esterification; nanostructures; thiols